Urban football narratives and the colonial process in Lourenço Marques - Domingos, Nuno (2013)
Support for Portuguese football teams, in Mozambique as well as in other former Portuguese colonies, could be interpreted either as a sign of the importance of a cultural colonial heritage in Africa or as a symbol of a perverse and neo-colonial acculturation. This article, focused on Maputo, the capital of Mozambique – formerly called Lourenc¸o Marques – argues that in order to understand contemporary social bonds, it is crucial to research the connection between the colonial process of urbanisation and the rise of urban popular cultures. Despite the existence of social discrimination in colonial Lourenc¸o Marques, deeply present in the spatial organisation of a city divided between a ‘concrete’ centre and the immense periphery, the consumption of football, as part of an emergent popular culture, crossed segregation lines. I argue that football narratives, locally appropriated, became the basis of daily social rituals and encounters, an element of urban sociability and the content of increasingly larger social networks. Therefore, the fact that a Portuguese narrative emerged as the dominant form of popular culture is deeply connected to the growth of an urban community.